Competition injuries in taekwondo: a literature review and suggestions for prevention and surveillance - Pieter, W.; Fife, G. P.; O'Sullivan, D. M. (British Journal of Sports Medicine, 2012)
Objective To review competition injuries in taekwondo and use this information to develop recommendations to reduce the number and severity of injuries in taekwondo competition.